2018
DOI: 10.1080/09513590.2018.1473360
|View full text |Cite
|
Sign up to set email alerts
|

Is gestational diabetes mellitus in obese women predicted by oxidative damage in red blood cells?

Abstract: Obesity in pregnant women has been associated with an increased risk of maternal complications, including gestational diabetes mellitus (GDM), a process that is related to oxidative stress (OS). To evaluate the biomarkers of OS in red blood cells (RBCs), we assigned 80 pregnant women to one of three groups: control (n = 28), overweight (n = 26) and obese (n = 26). Then, we measured in plasma, the levels of glucose, triacylglycerol (TAG), insulin, free fatty acids (FFAs), leptin and cytokines (e.g. interleukin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Studies from geographically and ethnically diverse populations have linked increased circulating AGEs and MDA to GDM. In this study, we also observed the positive associations of AGEs and MDA with GDM. However, the results of the mediation analyses showed no significant mediation by AGEs and MDA on the association of 3-PBA and 4F-3PBA with the risk of GDM.…”
Section: Resultssupporting
confidence: 75%
“…Studies from geographically and ethnically diverse populations have linked increased circulating AGEs and MDA to GDM. In this study, we also observed the positive associations of AGEs and MDA with GDM. However, the results of the mediation analyses showed no significant mediation by AGEs and MDA on the association of 3-PBA and 4F-3PBA with the risk of GDM.…”
Section: Resultssupporting
confidence: 75%
“… 17 Positive correlations between biomarkers of oxidative stress in RBC with GDM were discovered by previous study, suggesting the potential relationship between RBC and inflammatory response. 36 In addition, higher levels of RBC and HGB were accompanied with higher blood viscosity, which was reported to be a risk factor for insulin resistance. 37 The associations of RBC with insulin resistance and GDM need to be further confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies show increased lipid peroxidation (MDA, LOOH) [115][116][117][118][119] and significant changes in antioxidant status (total antioxidant capacity and antioxidant enzyme activity) in pregnant women with obesity [119][120][121][122][123] during the third trimester of pregnancy (Table 3). Another study has shown an increase in lipid peroxidation and protein carbonylation (PC) in pregnant women with obesity versus controls, only in the third trimester, but not in the first and second trimesters of pregnancy.…”
Section: Obesitymentioning
confidence: 99%
“…However, an increase in TNF-α was observed at 12-13 weeks of gestation, also in women with obesity who developed GDM. The ratio of reduced oxidized glutathione (GSH/GSSG) is an indirect marker of redox status [115]. In addition, increased antioxidant activity of SOD and CAT was observed in the placenta [122] and umbilical cord [119] of obese women compared to non-obese women, and compared to plasma activities during the third trimester of pregnancy.…”
Section: Obesitymentioning
confidence: 99%